Acute toxicity test of water and ethanol extract from african leaf (Gym-nanthemum amygdalina Del.) on zebra fish embrio (Danio rerio) - Lusi Agus Setiani; Ike Yulia Wiendarlina; Afifah Marissa Arlindini (Journal of Agriculture and Applied Biology, 2023)
Bitterleaf or African Leaf is a herbal plant empirically used to relieve fever and kidney disease. Pharmacological research reports that the leaves have antibacterial, anti-inflammatory, and antidiabetic properties, and a toxicity test was also conducted to ensure their safety. Therefore, this experiment aimed to obtain LC50 of African Leaf (Gymnanthemum amygdalina Del.) ethanol and water extract with the ZFET (Zebra Fish Embryo Acute Toxicity) method and also to observe the toxicity effect of zebrafish (Danio rario) embryo's morphology after the induction of the extract. The experiment refers to the OECD No.236 of 2013 as a guideline, and it was shown that African Leaf's ethanol extract LC50 values were obtained at 6.3629 ppm. Furthermore, the water extract LC50 value was obtained at 25.0520 ppm, and the African Leaf extract was categorized in the toxic category. The leaf extract has a harmful effect on zebrafish embryos, resulting in malformations of the tail, notochord, pericardium, and yolk sac.